Analisis Peran Guru Olahraga terhadap Minat Siswa pada Olahraga Ekstrakurikuler di Sekolah Menengah Pertama - Fadli Arbi; Renaldi Tumewu; Moh Syahfitra Massa; Safri Irawan; Meri Haryani (Performa, 2025)
This study aims to analyze the role of sports teachers in increasing student interest in extracurricular sports activities at the junior high school level. A literature review was conducted by reviewing various articles and previous studies that discuss factors influencing student participation in extracurricular sports, particularly the role of sports teachers. The results of the study indicate that sports teachers who have a supportive, communicative approach and are able to provide positive motivation play a key role in attracting student interest. In addition, teacher involvement in direct coaching and the quality of sports facilities at school also play an important role in increasing student participation. These findings emphasize the importance of developing sports teacher competencies and improving sports facilities at schools to encourage more active student participation in extracurricular sports activities